A retrospective analysis of the prosthetic joint infections of the hip and knee at a tertiary care center of India - Suresh Babu; Raju Vaishya; Hena Butta; Raman Sardana; Leena Mehndiratta; Yashpal Gulati; Yatinder Kharbanda; Havind Tandon (Apollo Medicine)
Introduction: An increase in the number of primary total joint arthroplasties has correspondingly led to an increase in revisions as a result of various complications. The prosthetic joint infection (PJI) is a major complication with concordantly increased morbidity and costs. Through this study, we aimed to determine the bacteriological profiles of PJI diagnosed at our institute and analyze them in the context of patient profiles, joints affected, and the center where the index procedure was done. Materials and Methods: A retrospective study of the revision surgeries for PJI in hip and knee arthroplasties during the period between 2014 and 2019 was conducted. An analysis of 43 patient profiles, with 29 of those being knees and the rest 14 being hips was done, concerning the clinical picture, microbiological profile, and co-morbidities. Results: PJI constituted 31.03% of the revision cases. The knee joint was involved in 67.44% (n = 29) and the hip joint in 32.56% (n = 14). Early infection was seen in 2 (4.65%) and late infections in the remaining 41 (95.34%). 51.66% (n = 22) were culture-positive PJI, whereas 48.34% (n = 21) were culture-negative (CN) PJI. Preoperative C-reactive protein was elevated in 46.51% of the patients (48.27% knees and 42.87% hips). The erythrocyte sedimentation rate was preoperatively elevated by 65.12%. Of the comorbidities PJI was associated with, diabetes mellitus in 30.23%, hypertension in 39.53%, hypothyroidism in 16.28%, skin disorders in 4.65% (psoriasis and eczema), and immunosuppression in 4.65% cases. Conclusions: Microbial growth on routine culture is not mandatorily positive in several clinically suspected PJI. Hence, a stringent protocol requires to be followed in the use of antibiotics, the collection and transportation of samples, and in the selection of media for cultures in the cases of PJI. Notwithstanding the limitations of this study, we conclude that bacterial infections do not follow any predictable patterns, and constant vigilance with a low threshold to suspect and investigate PJI is needed in the management of PJI. We propose based on our study findings that no antibiotics should be used only after a bacteriological diagnosis and antibiotic sensitivity is obtained, else it results in a high rate of CN PJIs.